2008
DOI: 10.1111/j.1365-2435.2008.01473.x
|View full text |Cite
|
Sign up to set email alerts
|

Bumble bee preference for flowers arranged on a horizontal plane versus inclined planes

Abstract: Summary 1.Determining factors affecting pollinator visitation is the key to understanding the reproductive success of animal-pollinated plants. The inclination of the ground where plants grow, which has been little studied, could be one such factor. There may be differences in foraging performance when visiting flowers on horizontal planes compared with flowers on inclines planes. And if this is the case, pollinators may have a preference for horizontal or inclined planes. To test these possibilities, a series… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 30 publications
0
5
0
1
Order By: Relevance
“…Like Leonard and Papaj (2011), we presented our flowers horizontally. This is a normal position for many flowers (Giurfa et al 1999), and is used in other studies of bumble bee floral orientation (e.g., Spaethe et al 2001). Makino (2008 also demonstrated that bumble bees prefer foraging on a horizontal as compared to a sloping array and had decreased foraging performance on a vertical as compared to a horizontal array.…”
Section: Discussionmentioning
confidence: 99%
“…Like Leonard and Papaj (2011), we presented our flowers horizontally. This is a normal position for many flowers (Giurfa et al 1999), and is used in other studies of bumble bee floral orientation (e.g., Spaethe et al 2001). Makino (2008 also demonstrated that bumble bees prefer foraging on a horizontal as compared to a sloping array and had decreased foraging performance on a vertical as compared to a horizontal array.…”
Section: Discussionmentioning
confidence: 99%
“…Coen & Nugent, 1994; Singer et al, 1999; Tucker & Grimes, 1999; Kellogg, 2000, 2007; Penin et al, 2002, 2005; Schmitz & Theres, 2005; Tooke et al, 2005; Vollbrecht et al, 2005; Benlloch et al, 2007; Bortiri & Hake, 2007; Conti & Bradley, 2007; Prusinkiewicz et al, 2007; Rebocho et al, 2008; Souer et al, 2008; Dumonceaux et al, 2009) and what forms are selected by pollination biological factors (e.g. Waddington, 1979; Waddington & Heinrich, 1979; Wyatt, 1982; Fishbein & Venable, 1996; Friedman & Harder, 2004; Harder et al, 2004; Jordan & Harder, 2006; Ishii et al, 2008; Makino, 2008; Classen‐Bockhoff, 2009), or by other aspects of reproductive biology (Campbell, 1989; Diggle, 2003) or climate (Stebbins, 1973; Prusinkiewicz et al, 2007). Prusinkiewicz et al (2007) discuss inflorescence morphospace and show which ramification patterns in inflorescences are common and which do not occur in nature.…”
Section: Systematic and Evolutionary Aspectsmentioning
confidence: 99%
“…While the exclusively horizontal presentation of our artificial flowers was not representative for all flower types visited by bumblebees, their size and general shape fell well within the natural range of flowers bumblebees typically forage from (Dafni & Kevan 1997, Dafni et al 1997). Moreover, choice experiments suggest that bumblebees prefer horizontally arranged flowers (Makino 2008), from which they also learn cues more flexibly (Wolf et al 2015), so that this type of flower is highly relevant for bumblebees. The colour contrast and spatial resolution of the patterns in our experiments were designed to ensure reliable detection by the bumblebees.…”
Section: Discussionmentioning
confidence: 99%